Optimization of home care visits schedule by genetic algorithm - Alves, Filipe (2020)
Currently, it has been verified that population is increasingly aged and it is necessary to perform home services. These services include home care visits to patients with impossibility of travel to healthcare centers, where the health professionals perform the medical treatments. Usually, this home care services are performed by nurses that need transportation for this purpose. Therefore, it is necessary to make a schedule of these home care visits that, usually, is made manually by the healthcare center. This work aims to carry out an automatic schedule of home care visits of the healthcare Center of Bragan¸ca, Portugal, in order to reduce the travel costs and optimize the time spent on trips. The Genetic Algorithm was used to solve this problem. In this paper it is presented the schedule of home care visits for three days of the healthcare center.